2014
DOI: 10.1002/cpdd.118
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rabeprazole granules versus tablets, and the effect of food on the pharmacokinetics of rabeprazole granules in healthy adults—cross‐study comparison

Abstract: The primary objective was to compare the pharmacokinetics (PK) of rabeprazole granules versus rabeprazole tablets, and assess the effect of food on the PK of rabeprazole granules. Data from three phase 1, open-label, single-dose, randomized, crossover studies in healthy adult participants are presented separately and as a cross-study comparison; study 1: PK of phase 1 rabeprazole granules versus rabeprazole tablets under fasting conditions; study 2: PK of phase 3 rabeprazole granules versus phase 1 rabeprazole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Previous studies on enteric coated formulations have reported benefits including rapid emptying into the small intestine which provides superior protection from the gastric environment; faster drug dissolution and absorption; and quicker onset of action for multiparticulate formulations compared to single unit tablets [21,22]. It is worth noting that these studies have been conducted in adults and little is known on the gastrointestinal transit of multiparticulate formulations in children [23].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on enteric coated formulations have reported benefits including rapid emptying into the small intestine which provides superior protection from the gastric environment; faster drug dissolution and absorption; and quicker onset of action for multiparticulate formulations compared to single unit tablets [21,22]. It is worth noting that these studies have been conducted in adults and little is known on the gastrointestinal transit of multiparticulate formulations in children [23].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the effect of food on rabeprazole capsule formulation was found to be considerable. In a randomized, open-label study of 53 healthy subjects, Thyssen et al [65] revealed that co-administration of a 10 mg DR rabeprazole capsule and a high-fat, highcalorie meal may lead to a significant decrease in both AUC 0-∞ and C max (by 27% and 55%, respectively) and a significant delay in t max as well (by 2 h).…”
Section: Food Effectmentioning
confidence: 99%
“…We are convinced that knowledge on this subject is vital to professionally educate patients with the aim to improve their compliance and increase the effectiveness of PPI therapy. -should be taken 60 min before a meal [40] -should be placed on the tongue to disintegrate and swallowed, with or without water [40] DR capsules ↓ AUC (by 35-38%) [34], ↓ C max (by 24-40% and 58-63%, depending on the study) [36,38], ↑ t max (by 2 h) [36] -should be taken 60 min before a meal [33] -should be swallowed whole or with content mixed with 15 mL of applesauce [33] DR granules for oral suspension no studies found -should be taken 60 min before a meal [33] -should be mixed with 5-15 mL of water [33] DR tablets no significant changes in AUC and C max , ↑ t max (by 1.3 h) [41] -can be taken with or without food [41] -should be swallowed whole with water [41] -can be taken with or without food [56,59] -should be swallowed whole with water [56,59] -preferably should be administered in the morning [61] DR granules for oral suspension ↓ AUC (by 29%), ↓ C max (by 51%), ↑ t max (by 2 h) [56] -should be taken 30 min before a meal [56] -content should be sprinkled into 5 mL of applesauce/apple juice [56,62] -do not mix with water or other liquids or food [56] Rabeprazole DR capsules ↓ AUC (by 27%), ↓ C max (by 55%), ↑ t max (by 2 h) [65] -should be taken 30 min before a meal [63] -content should be sprinkled onto a small amount of applesauce/apple juice/yoghurt/fruit or vegetable-based baby food/infant formula/pediatric electrolyte solution [63,65] -can be administered both in the morning or in the evening [67] -evening intake can be beneficial for patients with nocturnal acid breakthrough or nocturnal reflux [66] DR tablets no significant changes in AUC and C max , ↑ t max (by 2.5 h) [42] no significant changes in median intragastric pH [23,24] -can be taken with or with...…”
mentioning
confidence: 99%
“…passage through the pyloric sphincter, as observed with a quicker onset of action for multi-particulate formulations compared to single unit tablets (74,75). However, it should be noted that there is currently no evidence on the relative gastric emptying or intestinal transit time of liquid and solid oral dosage forms in pediatric populations.…”
Section: N C L U S I O N Criteriamentioning
confidence: 99%